Micro and nano analysis of a novel polymeric bioresorbable scaffold and its drug release - Mahmood, Tamara (2018)
The composition of the top-most molecular layers of solid materials is of great importance in the understanding of many technologically important processes. This is especially so, for example for devices exposed to the in vivo environment of our bodies especially if long term functionality is required. Cardiovascular stents or scaffolds are a biomedical implant that must maintain structural and functional integrity for periods of months to achieve their therapeutic goal. In this work, the fully polymeric drug-eluting bioresorbable scaffold, ArterioSorbTM is characterised, paying particular attention to surface and near surface properties. The introduction of cardiovascular stents has considerably enhanced the potential of surgical intervention via angioplasty. Biomaterials used for implants may be metallic, ceramic, polymeric or composite. A new generation of drug eluting stent are now emerging, such as the Poly(L-lactide) (PLLA) based fully biodegradable stents studied here, that have the potential to increase the therapeutic potential of this approach even further. PLLA is a bioabsorbable semi-crystalline polymer that possesses a low elongation and high tensile strength, which makes it appropriate for this medical application. Using a spray-coating method a sirolimus/PDLLA layer was coated onto the surface of a bioresorbable PLLA scaffold by Arterius Ltd. The aim of this thesis is the study of the drug distribution and physiochemical properties of the biomedical device and to relate this information to likely drug release mechanisms under physiological conditions. Complementary surface and near-surface analysis techniques including scanning electron microscopy (SEM), atomic force microscopy (AFM), time-of-flight secondary ion mass spectrometry (ToF-SIMS), X-ray photoelectron spectroscopy (XPS) and confocal Raman imaging (CRM) have been used to assess structure, composition and their relation to drug release. Primarily, this work was carried out on a series of extruded and orientated (die-drawn) PLLA tubing before considering the actual bioresorbable medical device (uncoated, coated expanded and crimped scaffolds). ToF-SIMS has been used to confirm the chemical homogeneity of the PLLA coating and provide evidence of some minor surface elemental contamination likely due to transfer of fluorine from packaging/sample handling. The drug (sirolimus) was clearly observed and mapped at the microscale at the surface and in the bulk of the scaffold coating. In addition, the physical properties of these materials were investigated using nano and micro thermal analysis. The percentage of crystallinity of the PLLA materials was studied using Differential Scanning Calorimetry (DSC). Attenuated total reflection infrared (ATR-IR) helped in assessing the structure of PLLA. Factors including the manufacturing process used have been shown to have an effect on the materials. The degradation in vitro has been shown to be influenced by the molecular weight of the polymer and the concentration of the drug. This thesis is organised into six chapters. Chapter 1 provides an introduction to the technical requirements needed for bioresorbable stent and outlines the literature review and research context for the development of the scaffold, including materials used for the manufacturing of the scaffold, spray coating method and laser cutting techniques. Chapter 2 describes the instrumentation and methodology used for characterising such medical device as well as a description of laser cutting used in manufacture. Chapter 3 presents a feasibility study on the extruded and oriented tubing. Chapter 4 describes the characterisation of the drug distribution in the drug/polymer matrix. Chapter 5 provides a detailed characterisation of the in vitro degradation of sirolimus/PDLLA coating layer revealing the release kinetics of the device. Finally, Chapter 6 gathers information learnt throughout this thesis and explored future directions to improve release and performance of such a device.